2018
DOI: 10.1177/1541204018806976
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Race and Juvenile Court Decision-Making: A Counterfactual Approach

Abstract: Prior research has found that disproportionate minority contact (DMC) is a problem at various decision-making points in the juvenile justice system. This study addresses two limitations often found in prior DMC research: (1) a focus on a single court and/or a single stage of the juvenile court process and (2) methodological problems in comparing youth of different races who are otherwise similarly situated. Nearest neighbor matching is used to examine the relationship between race and five juvenile court outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…3 Of this research, the individual effect of race on transfer decisions has resulted in conflicting findings (Puzzanchera & Hockenberry, 2015). Some studies reported that a juvenile’s race predicts waiver (Bishop & Frazier, 1996; Brown & Sorensen, 2013; Cheesman et al, 2010; Gann, 2018; Mears & Field, 2000), while other studies suggest no relationship (Cauffman et al, 2007; Leiber & Mack, 2003; Mears et al, 2014; Poulos & Orchowsky, 1994).…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…3 Of this research, the individual effect of race on transfer decisions has resulted in conflicting findings (Puzzanchera & Hockenberry, 2015). Some studies reported that a juvenile’s race predicts waiver (Bishop & Frazier, 1996; Brown & Sorensen, 2013; Cheesman et al, 2010; Gann, 2018; Mears & Field, 2000), while other studies suggest no relationship (Cauffman et al, 2007; Leiber & Mack, 2003; Mears et al, 2014; Poulos & Orchowsky, 1994).…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…Although there have been hundreds of studies of racial and ethnic disparities in the juvenile justice system (see Spinney et al, 2018), studies that focus on multiple states are not as common. In addition, despite a recent increase in studies that examine multiple jurisdictions (see, e.g., Gann, 2019), no studies to date have examined differences in DMC across them. This gap is notable given the mixed evidence of racial and ethnic disparities across multiple stages of juvenile justice processing (see Bishop & Leiber, 2012;Bishop, Leiber, & Johnson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Secure confinement can be considered the most severe outcome in the juvenile justice system, given its lifelong consequences noted above. Disproportionate confinement is also evident postadjudication (Gann, 2019), though perhaps less so than at the preadjudication stage (Spinney et al, 2018). Only 5 of 13 reviewed disproportionate minority contact studies found overrepresentation or mixed findings for Latinx adolescents, and 10 of 20 studies noted Black adolescents were overrepresented or demonstrated mixed findings in use of postadjudication secure confinement (Spinney et al, 2018).…”
mentioning
confidence: 99%
“…Black and Latinx adolescents are overrepresented among youth in preadjudication detention (Chappell, 2019; Gann, 2019; Guevara et al, 2006; Lowery & Smith, 2020). Preadjudication detention is significantly associated with decreased likelihood of more favorable outcomes in later court processing, such as probation versus secure confinement (Cochran & Mears, 2015; Guevara et al, 2018).…”
mentioning
confidence: 99%